2017
DOI: 10.2147/dddt.s131892
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of triamterene as an inhibitor of the TGR5 receptor: identification in cells and animals

Abstract: BackgroundG-protein-coupled bile acid receptor 1 (GPBAR1, also known as TGR5) has been shown to participate in glucose homeostasis. In animal models, a TGR5 agonist increases incretin secretion to reduce hyperglycemia. Many agonists have been developed for clinical use. However, the effects of TGR5 blockade have not been studied extensively, with the exception of studies using TGR5 knockout mice. Therefore, we investigated the potential effect of triamterene on TGR5.MethodsWe transfected the TGR5 gene into cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…While our data are consistent with previous work demonstrating that TGR5 ablation contributes to metabolic dysregulation in mouse models [ 3 , 19 , 34 , 37 , 49 ], our data are the first to demonstrate that TGR5 signaling specifically within the hepatocyte plays a significant role in whole body glucose regulation. Until now, the role of TGR5 in the maintenance of glucose homeostasis and insulin sensitivity has been attributed to its effects on mitochondrial function in muscle and BAT and/or insulin release from the pancreas, enhanced by enteroendocrine L cell GLP-1 secretion [ 3 , 13 , 14 , 15 , 17 , 20 ]. For example, various TGR5 agonists have been shown to ameliorate glucose intolerance in obese and diabetic mice [ 3 , 13 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our data are consistent with previous work demonstrating that TGR5 ablation contributes to metabolic dysregulation in mouse models [ 3 , 19 , 34 , 37 , 49 ], our data are the first to demonstrate that TGR5 signaling specifically within the hepatocyte plays a significant role in whole body glucose regulation. Until now, the role of TGR5 in the maintenance of glucose homeostasis and insulin sensitivity has been attributed to its effects on mitochondrial function in muscle and BAT and/or insulin release from the pancreas, enhanced by enteroendocrine L cell GLP-1 secretion [ 3 , 13 , 14 , 15 , 17 , 20 ]. For example, various TGR5 agonists have been shown to ameliorate glucose intolerance in obese and diabetic mice [ 3 , 13 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGR5 signaling in many of these tissue types has been shown to contribute to glucose regulation [ 3 , 13 ]. For example, in gastrointestinal enteroendocrine L cells, TGR5 signaling promotes glucagon-like peptide-1 (GLP-1) secretion [ 3 , 14 , 15 ]. Furthermore, in mice fed a high fat diet (HFD), TGR5 agonists have been shown to increase in GLP-1 secretion from L cells, which was associated with an improvement in insulin sensitivity and measures of hepatic steatosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, triamterene also attenuated the effect of imperatorin in a dose-dependent manner. In a recent study, triamterene specifically blocked TGR5 [ 32 ]. Therefore, imperatorin can activate TGR5 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this effect of imperatorin was inhibited by triamterene. It has been reported that triamterene possesses a TGR5 blocking-like action as a pleiotropic effect in addition to K + -sparing [ 32 ]. The functional blockade of TGR5 by triamterene supports that imperatorin mediates TGR5.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies revealed that TGR5 signaling regulates glucose tolerance, inflammation, and energy expenditure [ 9 , 13 , 14 , 15 ], such that TGR5 is now recognized as a potential target for the treatment of metabolic disorders. To this end, much metabolic research regarding TGR5 signaling has focused on TGR5-mediated effects on GLP-1 secretion from enteroendocrine L cells [ 9 , 16 , 17 ], mitochondrial thermogenesis in adipocytes [ 13 , 18 , 19 ], and decreased inflammatory cytokine secretion from immune cells [ 1 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%